Doppler ultrasound peak systolic velocity versus end tidal carbon dioxide during pulse checks in cardiac arrest. (February 2023) - Haddad, Ghania; Margius, Deanna; Cohen, Allison L.; Gorlin, Margaret; Jafari, Daniel; Li, Timmy; Owens, Casey; Becker, Lance; Rolston, Daniel M.
Abstract: Background: An accurate, non-invasive measure of return of spontaneous circulation (ROSC) is needed to improve management of cardiac arrest patients. Objectives: During a pulse check in Emergency Department (ED) cardiac arrest patients, we compared the correlation between 1) end tidal carbon dioxide (ETCO2 ) and systolic blood pressure (SBP), and 2) Doppler ultrasound peak systolic velocity (PSV) and SBP. Additionally, we assessed the accuracy of PSV ≥ 20 cm/sec in comparison to previously suggested ETCO2  ≥ 20 or ≥ 25 mmHg thresholds to predict ROSC with SBP ≥ 60 mmHg. Methods: This was a secondary analysis of a previously published prospective observational study of ED cardiac arrest patients with an advanced airway and femoral arterial line in place. During each pulse check, highest SBP, highest PSV, and ETCO2 at the end of the pulse check were recorded. Spearman correlation coefficients were calculated and compared using a Fisher Z-transformation. Accuracy of previously determined PSV and ETCO2 thresholds for detecting ROSC with SBP ≥ 60 mmHg were compared using McNemar's tests. Results: Based on data from 35 patients with 111 pulse checks, we found a higher correlation between PSV and SBP than ETCO2 and SBP (0.71 vs 0.31; p < 0.001). Diagnostic accuracy of PSV ≥ 20 cm/sec for detecting ROSC with SBP ≥ 60 mmHg was 89% (95% CI: 82%-94%) versus 59% (95% CI: 49%-68%) and 58% (95% CI: 48%-67%) for ETCO2  ≥ 20 and ≥ 25 mmHg, respectively. Conclusions: During a pulse check, Doppler ultrasound PSV outperformed ETCO2 for correlation with SBP and accuracy in detecting ROSC with SBP ≥ 60 mmHg.